2016
DOI: 10.1002/2016jb013243
|View full text |Cite
|
Sign up to set email alerts
|

Contrasts in compliant fault zone properties inferred from geodetic measurements in the San Francisco Bay area

Abstract: In crustal fault zones, regions of damaged rock characterized by reduced elastic shear modulus can influence patterns of near‐field interseismic deformation. In order to study these compliant fault zones (CFZs) and how they might develop over the lifetimes of faults, we compare two fault segments with contrasting fault age and lithology along the San Andreas Fault in the San Francisco Bay Area. New geodetic measurements of the interseismic velocity fields at each location are used to constrain fault zone param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…The broad transition zone would also exist for large values of the nucleation size, a scenario that we do not focus on in this study. The geodetically estimated locking depth D glock based on an elastic dislocation model is a convenient way to compare our modeling results with observations, since it is still commonly used [e.g., Chen and Freymueller , ; Jolivet et al , ; Lindsey and Fialko , ; Lindsey et al , ; Materna and Bürgmann , ]. The time‐dependent surface deformation driven by viscoelastic processes can be equivalently mapped into time‐dependent fault slip rates and locking depths in half‐space models [ Savage , ; Meade and Hager , ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The broad transition zone would also exist for large values of the nucleation size, a scenario that we do not focus on in this study. The geodetically estimated locking depth D glock based on an elastic dislocation model is a convenient way to compare our modeling results with observations, since it is still commonly used [e.g., Chen and Freymueller , ; Jolivet et al , ; Lindsey and Fialko , ; Lindsey et al , ; Materna and Bürgmann , ]. The time‐dependent surface deformation driven by viscoelastic processes can be equivalently mapped into time‐dependent fault slip rates and locking depths in half‐space models [ Savage , ; Meade and Hager , ].…”
Section: Discussionmentioning
confidence: 99%
“…Compliant shallow fault zone structures have been inferred from seismic and geodetic studies for a number of faults, including Eastern California Shear Zone [ Fialko et al , ; Cochran et al , ], northern San Andreas fault [ Chen and Freymueller , ; Jolivet et al , ; Materna and Bürgmann , ], and San Jacinto fault [ Allam and Ben‐Zion , ; Lindsey et al , ]. Neglecting such features in inverting geodetic data often leads to underestimated locking depths [ Chen and Freymueller , ; Jolivet et al , ; Lindsey et al , ].…”
Section: Discussionmentioning
confidence: 99%
“…Wilson et al 2003;Gudmundsson 2007), but some observations might suggest that the outer and less damaged part could reach a few kilometres width (e.g. Faulkner et al 2003;Wilson et al 2003;Gudmundsson 2007;Materna & Bürgmann 2016;Perrin et al 2016b). Damage zones can have a non-negligible impact on rupture dynamics, stresses and slip estimates (e.g.…”
Section: Damage Zonementioning
confidence: 99%
“…By defining structural maturity based on fault slip, slip rate, age, and length, Perrin et al () showed for 27 large continental earthquakes that the largest earthquake slip on each fault occurred on fault sections with the most compliant rocks. The interseismic velocity fields measured from northern San Andreas fault also suggested highly variable fault zone structure along strike (Chen & Freymueller, ; Jolivet et al, ; Materna & Bürgmann, ). Damaged fault zones were observed at Lake San Andreas and Bodega Bay but not at Black Mountain and Point Reyes that are 30–40 km south, respectively, indicating the critical roles of fault lithology and tectonic setting in sustaining fault zone damage in addition to cumulative displacement (Materna & Bürgmann, ).…”
Section: Introductionmentioning
confidence: 99%
“…The interseismic velocity fields measured from northern San Andreas fault also suggested highly variable fault zone structure along strike (Chen & Freymueller, ; Jolivet et al, ; Materna & Bürgmann, ). Damaged fault zones were observed at Lake San Andreas and Bodega Bay but not at Black Mountain and Point Reyes that are 30–40 km south, respectively, indicating the critical roles of fault lithology and tectonic setting in sustaining fault zone damage in addition to cumulative displacement (Materna & Bürgmann, ). It also implies that the along‐strike variation in fault zone rock properties is likely a common feature on major strike‐slip faults where the lithology and tectonic setting vary along strike.…”
Section: Introductionmentioning
confidence: 99%